Perilaku Agresif Konteks Pendidikan Karakter Telaah terhadap Al Qur'an dan Tasfirnya (SAP (Susunan Artikel Pendidikan), 2024)
The development of a positive personality can have a detrimental effect on the learning environment. This study aims to examine the concept of aggressive behavior from the perspective of the Qur'an and its interpretation and how character education can be an effective solution in overcoming this phenomenon. Based on the study of the verses of the Qur'an, which teach about the importance of gentleness and self-control, it is clear that Islam encourages its people to stay away from acts of violence and aggressive behavior. The interpretation of scholars also emphasizes that aggressive behavior is contrary to the values of humanity and moral principles taught in Islam. Therefore, character education based on the values of the Qur'an is very important in forming positive behavior in students, reducing aggressive behavior, and creating a conducive educational environment. This study uses a qualitative approach with a literature review method, namely reviewing literature related to the discussion. The purpose of the study with character education based on the values of the Qur'an is very important in forming positive behavior of students, reducing aggressive behavior, and creating a conducive educational environment.